IMPLEMENTATION OF SUGENO FUZZY LOGIC ON A RICE-EATING BIRD REPELLENT IN RICE FIELDS TO HELP FARMERS BASED ON MICROCONTROLLERS - Ikhsan, Muhammad; Hasugian, Abdul Halim; Gunawan, Gunawan (UIN Sumatera Utara, 2022)
The rapid development of technology in the current era, especially in the field of sensors, has made many technologies that use sensors appear. In the agricultural sector itself, the use of sensor technology is not spared. In the agricultural sector, rice fields also require a tool that can detect pests which are usually done by the manual method. The purpose of this research is to help farmers repel bird pests with automation tools to make it easier to monitor the fields from pests. This study conducted experiments carried out by manipulating the research object. The tools used are Arduino Uno microcontrollers as tool controllers, PIR sensors as detection sensors and servo motors as tool drivers. When a pest is detected by the sensor it is then sent to the device controller in the form of Arduino after which the servo motor moves. From the results of testing all the components of the tool, it can be concluded that the results of the entire system work and function in accordance with the system design, the results of the PIR sensor test can detect objects that pass through the sensor with an average of 120 cm